2004
DOI: 10.1158/1055-9965.468.13.3
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Factors in Helicobacter pylori-Related Gastric Precancerous Lesions in Venezuela

Abstract: Although Helicobacter pylori (HP) infection has been acknowledged to play an etiological role in gastric carcinogenesis, its relatively weak association particularly in developing countries suggests critical roles of cofactors. Among a population with an extremely high prevalence of HP infection (≈95%) in Venezuela, we examined the relationship of household characteristics, smoking, alcohol drinking, dietary consumption, and plasma nutrient levels with the prevalence of three different stages of gastric precan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…In a study [ 176 ] from South Korea in which 199,235 patients without IM were followed up, a dose-dependent increase in the risk of IM in smokers was found, and this risk was significantly reduced in those who had quit smoking. This dose-dependent correlation was also confirmed in other studies [ 177 , 178 ].Smoking is not only related to the occurrence of PLGC but also to disease severity. Long-term smokers exhibited a significantly increased risk of severe CAG and IM [ 179 181 ].…”
Section: Treatmentsupporting
confidence: 90%
See 1 more Smart Citation
“…In a study [ 176 ] from South Korea in which 199,235 patients without IM were followed up, a dose-dependent increase in the risk of IM in smokers was found, and this risk was significantly reduced in those who had quit smoking. This dose-dependent correlation was also confirmed in other studies [ 177 , 178 ].Smoking is not only related to the occurrence of PLGC but also to disease severity. Long-term smokers exhibited a significantly increased risk of severe CAG and IM [ 179 181 ].…”
Section: Treatmentsupporting
confidence: 90%
“…A case-control study of American veterans showed that smoking was an independent risk factor for IM [170]. This finding was also supported by another case-control study from the northwestern part of China [168]. A study involving 7302 Chinese patients with chronic gastritis also suggested that smoking was an independent risk factor for the occurrence of PLGC [165].…”
Section: Statement 34 a History Of Long-term Smoking Significantly In...mentioning
confidence: 68%
“…Smoking has been reported to be a risk factor for GAC, causing a 60 and 20% increase in GAC risk for men and women, respectively ( Nagaich, 2018 ). In premalignant lesions, smoking has been reported to be associated with IM, but not with CAG ( Kato et al, 2004 ; Peleteiro et al, 2007 ; Kim et al, 2019 ; Muhsen et al, 2019 ). In our study, we did not find a significant association between CAG and smoking.…”
Section: Discussionmentioning
confidence: 97%
“…The intestinal subtype accounts for $70% of gastric cancer cases (3) and is characterized as having a preneoplastic sequence spanning from chronic superficial gastritis to atrophic gastritis, intestinal metaplasia, dysplasia and ultimately malignancy (4,5). Several case-control studies of gastric precancerous lesions, predominantly atrophic gastritis and intestinal metaplasia, have identified common risk factors for gastric cancer such as cigarette smoking, old age and low levels of fruit or vitamin C intake (6,7,8,9,10,11). Studies of gastric precancerous lesions may improve our understanding of the biologic basis of carcinogenesis and the natural history of gastric cancer.…”
Section: Introductionmentioning
confidence: 99%